Assessment of CPT Data on Liquefaction Mitigation with Rammed Aggregate Piers® - Bal, E. Kurt; Oner, L.; Ozaydin, I. K.; Edil, T. B. (SPRINGER-VERLAG SINGAPORE PTE LTD, 2022)
This paper presents the results of pre- and post-improvement cone penetration test (CPT) results executed at the site where Rammed Aggregate Pier (R) elements were used for the liquefaction mitigation. The effectiveness of these elements is attributed to the lateral pre-stressing that occurs in the matrix soil during construction and to the high strength and stiffness of the piers. The improvements provided by Rammed Aggregate Pier (R) elements mitigate liquefaction potential include (i) soil densification (ii) transferring a major portion of the seismically induced shear stresses from the soil to columns (iii) increasing the horizontal stress of the surrounding soil (iv) dissipation of excess pore water pressure. In the case history presented in this paper, the soil profile consisted of a thick hydraulic fill layer (characterized by silty, clayey sand) overlying sea bottom sediments of soft to medium stiff silty clay (CL) and medium stiff silty clay with sand (SM) down to almost 40 m depth which are underlain by a stiff to very stiff silty clay layer. Installation of 50 cm diameter Rammed Aggregate Pier (R) elements which are constructed by Impact (R) System construction procedures (bottom-feed dry displacement method) is aimed to mitigate liquefaction risk in the hydraulic fill layer and to limit settlements, by forming an improved soil crust of desired thickness at the surface. Rammed Aggregate Piers of 16 m length were installed in square and triangular patterns with 1.5 m and 1.7 m on-center spacing, respectively. CPT testing was performed before and after the installation of the piers. The results show that the additional densification and improvement in non-cohesive soils due to vibration and ramming during the pier construction has increased the safety factor against liquefaction by 2.5-3.0 times.
Keywords: Impact (R) System; Rammed aggregate pier (R); Liquefaction mitigation; Cone penetration test (CPT); Engineering; Transportation